Towards a national language policy for Cameroon - (:unkn) unknown (My University, 2013)
If language constitutes a fundamental defining feature of human existence, then it means that a country's language policy options signal the development orientations established for that country. Accordingly choosing between indigenous and foreign languages directly implies choices between development and underdevelopment. In this light, the underdevelopment of Africa crucially hinges on the inappropriate choice of language policy adopted at independence or the failure to ensure the implementation of those considered to be significantly appropriate. In Cameroon, the case is clear. Despite the country's rich linguistic diversity, we have continued to implement a language policy that is based on foreign languages that falls short of responding adequately to the needs and aspirations of citizens. At this historic moment of reunification commemoration, the demands of a thorough review of this policy are enormous and their implications far-reaching. The need for an integrative policy, in fact, one that carefully considers the country's socio-cultural and political landscape is not only real but also urgent.
Keywords: African Research